2017
DOI: 10.1103/physreve.95.053101
|View full text |Cite
|
Sign up to set email alerts
|

Stability of viscous film flow coating the interior of a vertical tube with a porous wall

Abstract: This is the final published version of the article (version of record). It first appeared online via APS Physics at https://doi.org/10.1103/PhysRevE.95.053101 . Please refer to any applicable terms of use of the publisher. University of Bristol -Explore Bristol Research General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms PHYSICAL REVIE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 34 publications
4
12
0
Order By: Relevance
“…Using the low-dimensional model introduced in Dietze & Ruyer-Quil (2015), which had been applied only to gravity-free films, we have performed spatio-temporal computations of spatially-evolving falling films and computed travelling-wave solutions through numerical continuation. Our model extends upon the earlier works of Trifonov (1992), Camassa et al (2014Camassa et al ( , 2017, Zhou et al (2016), Liu & Ding (2017), and Ding et al…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Using the low-dimensional model introduced in Dietze & Ruyer-Quil (2015), which had been applied only to gravity-free films, we have performed spatio-temporal computations of spatially-evolving falling films and computed travelling-wave solutions through numerical continuation. Our model extends upon the earlier works of Trifonov (1992), Camassa et al (2014Camassa et al ( , 2017, Zhou et al (2016), Liu & Ding (2017), and Ding et al…”
Section: Resultssupporting
confidence: 88%
“…The model employed in our current study extends upon the earlier works of Trifonov (1992), Camassa et al (2014Camassa et al ( , 2017, Zhou et al (2016), Liu & Ding (2017), and Ding et al (2019) by accounting for axial viscous diffusion and inertia. This has allowed us to investigate four real liquids, for which we determine the lower and upper occlusion bounds…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Halpern & Wei (2017) determined that for films coating a fibre, slip at the wall resulted in larger drops; their results suggested a possible explanation for slight discrepancies between no-slip models and the experiments of Quéré (1990). For a falling film inside a tube, Liu & Ding (2017) extended the long-wave model of Camassa et al (2014) to account for slip due to a porous wall. Their numerical simulations and classification of instabilities as absolute or convective demonstrated that slip promotes plug formation.…”
Section: Introductionmentioning
confidence: 99%
“…As a common situation in interstifial flow, thin liquid film flowing on porous medium exhibits interesting dynamical phenomena. Ding and Liu [26,27] discovered that the film flowing on a porous vertical cylinder was more unstable and the increasing permeability of the porous medium significantly enhanced the destabilizing effect. The slippery effect often has a connection with wettability and porosity of the materials [28][29][30].…”
Section: Introductionmentioning
confidence: 99%